If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4h + -70 = 12h + 2 Reorder the terms: -70 + 4h = 12h + 2 Reorder the terms: -70 + 4h = 2 + 12h Solving -70 + 4h = 2 + 12h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-12h' to each side of the equation. -70 + 4h + -12h = 2 + 12h + -12h Combine like terms: 4h + -12h = -8h -70 + -8h = 2 + 12h + -12h Combine like terms: 12h + -12h = 0 -70 + -8h = 2 + 0 -70 + -8h = 2 Add '70' to each side of the equation. -70 + 70 + -8h = 2 + 70 Combine like terms: -70 + 70 = 0 0 + -8h = 2 + 70 -8h = 2 + 70 Combine like terms: 2 + 70 = 72 -8h = 72 Divide each side by '-8'. h = -9 Simplifying h = -9
| -7.678+(-29)= | | 8.3x-18=9x | | 14y-13y=13 | | (5x-7)+(3x+8)= | | (u-7)*10=70 | | -3/4a | | 45x^4-100x+55=0 | | g-1= | | g(x)=5x+65 | | 2y^2-4y-20=0 | | 2x-8+5x-32=180 | | 3a+6+4= | | 2x-6+90+48=180 | | (q+7)*5=45 | | 90+y+2+3y=180 | | g(x)=-4x+15 | | 50-4x=-61-6x | | 7m-6m=4 | | 4+[7-m]=5 | | (5*5)+(b*b)=(16*16) | | 25x-27x=7-9 | | 5k-4k=6 | | 3x-5=7k+7 | | 2x+2=4x+2+x | | g(x)=-4x+30 | | 11+2lnx=4 | | 3(c-9)=3 | | 2c^4-6c^3=12c^2+36c | | 3x+3x-7=65 | | K+20=7 | | x+90+x+4=180 | | 1=2-d |